Retronychia - Cristina Diniz Borges Figueira de Mello; Milena da Rocha e Souza; Leandro Fonseca Noriega; Nilton Di Chiacchio (Sociedade Brasileira de Dermatologia, 2018)
Abstract: Retronychia is a recently described disorder caused by ingrowth of the proximal nail plate into the proximal nail fold. It is suspected when there is persistent paronychia, particularly in the setting of trauma. This disease is probably underdiagnosed due to limited knowledge among dermatologists and the presence of incomplete clinical forms. Nail plate avulsion is the diagnostic and curative procedure of choice, despite reports of relapse.